Seasonal plant-microbial coupling regulates carbon transformation pathways and soil organic carbon persistence in alpine grasslands - Na Li; Yalin Wang; Shanshan Li; Tianwei Xu; Lin Wei; Shixiao Xu; Na Zhao (CATENA, 2026)

Characterization of phosphorylated whey protein and its hydrolytic insoluble peptide aggregates - Hui Yang; Ru Lin; Yinuo Xiao; Xuan Shang; Shanshan Bai (International Dairy Journal, 2026)

Metagenomic indications of potential pathogen-associated and antibiotic resistance risks following UV–chlorine disinfection in sprout production - Yufei Wei; Lin Zhu; Xiangfu Jin; Huangli Yao; Shanshan He; Pu Feng; Feihong Yu; Yulu Xiang; Zhiheng Li; Shanying He (Environmental Pollution, 2026)

Robust classification of dental tissues using LIBS data based on data reconstruction and distance prior strategy - Shuting Lin; Xingwei Yi; Lei Yan; Shanshan Liang; Fusong Yuan (Analytica Chimica Acta, 2026)

Establishing robust chronologies in mangrove sediments in Southeast China with synergistic application of 210Pb and dual 137Cs markers - Shengbin Ye; Qiangqiang Zhong; Conghe Zhang; Shanshan Song; Xin'ao Guo; Neil Saintilan; Guanghui Lin (Quaternary International, 2026)

Long-term increases in tree water-use efficiency across China are associated with CO2 and hydroclimatic variation - Yali Ding; Li Wen; Jingzhi Zhang; Wei Zhang; Hongsong Chen; Shanshan Song; Zongrui Lai; Jinxing Zhou; Guanghui Lin (Journal of Hydrology, 2026)

Unraveling the anti-listerial activity of noni fruit essential oil: Omics-based mechanistic insights and application in salmon preservation - Qiongping Hong; Jiamu Kang; Xinyu Li; Shanshan Zheng; Ming Yang; Lin Zhang; Yuyun Lu (International Journal of Food Microbiology, 2026)

Polygonatum kingianum polysaccharides ameliorate cognitive impairments in alcohol-exposed obese mice in a sex-specific manner by regulating the gut microbiome and metabolome - Jiayao Lv; Yizhe Qu; Qixin Yan; Ken Cheng; Qingyang Wu; Jiayi Zhang; Xinting Duan; Shanshan Han; Honglei Tian; Lin Shi (Food Research International, 2026)

Broad-specificity antibody profiled by hapten prediction for immunoassay development of anilinopyrimidine fungicides - Shiqi Lin; Liqiang Liu; Yingyue Zhu; Shanshan Song; Hua Kuang; Chuanlai Xu; Lingling Guo (Food Chemistry, 2026)

Triazine and other herbicides in sediments of lower Laurentian Great Lakes – pre- and post-depositional mobility and in-situ degradation - Shanshan Zhou; Huan He; Tian Lin; Jiehong Guo; Xiusen Yang; Xinyue Jia; Neil C. Sturchio; Karl J. Rockne; John P. Giesy; An Li (Environmental Pollution, 2026)

Microbially induced hydroxyapatite improves simultaneous nitrogen and phosphorus removal in aerobic granular sludge - Fan Yang; Gonglei Wang; Shanshan Xu; Dexin Lin; Rui Yang; Peng Yan; Youpeng Chen; Jinsong Guo; Fang Fang (Bioresource Technology, 2026)

Size-resolved airborne particle control in a dental operatory: field comparison of window opening, portable air purifier, and UV air disinfection - Chen Chen; Di Zhang; Xiaoyi Xiao; Chuanhao Wang; Ruixin Nie; Xiaojing Lin; Mengmeng Cao; Meiqiu Hong; Yanjun Su; Bin Zhao; Shanshan Shi; Mingyao Yao; et al. (Building and Environment, 2026)

Simultaneous plasma catalytic degradation of dimethyl sulfide and methyl mercaptan with reduced graphene oxide modified manganese oxide - Wenji Feng; Mengyu Liu; Nan Lin; Shanshan Guo; Haiqiang Wang; Zhongbiao Wu (Journal of Hazardous Materials, 2026)

Enhanced removal of iodine ions using Zn-based metal-organic framework/polypyrrole adsorption membrane - Lingyun Xu; Shanshan Lu; Liping Jiang; Xiaohe Tian; Xijie Lin; Jianhua Qiu (Journal of Environmental Sciences, 2026)

Synergistic modification of rice starch by ultrasound and yeast polysaccharides: Insight into the structural and physicochemical properties - Jingjing Jiang; Zhonghua Yuan; Peili Lin; Shanshan Chen; Zhuo Zheng; Shensheng Xiao; Xuedong Wang; Yang Fu (Journal of Cereal Science, 2026)

Optimized cryoablation and combinatorial chemotherapy overcome sublethal survival in pancreatic cancer cells - Yukun Cao; Xin Li; Jing Shen; Shanshan Xie; Haoyang Lin; Yuling Luo; Xinli Zhou (International Journal of Refrigeration, 2026)

Cold plasma treatment of noni juice: A dual strategy for flavor improvement and bioactivity enhancement - Xinyu Li; Jiamu Kang; Qiongping Hong; Shanshan Zheng; Lin Zhang (Food Chemistry, 2026)

Flavor and quality evolution during storage of fermented noni juice: Integrated insights from E-–sensory evaluation, HS-SPME-GC–MS and LC-MS/MS - Qiongping Hong; Shanshan Zheng; Jiamu Kang; Yixia Zeng; Haiming Chen; Congfa Li; Lin Zhang (Food Chemistry, 2026)

Revealing the flavor deterioration and key off-odor compounds in garlic paste during processing and storage: A complementary approach with GC-MS, GC-IMS, and GC-O-MS - Weihe Zhu; Lu Xiang; Yunge Liu; Shanshan Zhou; Rui Lin; Zhenjia Zheng; Rentang Zhang; Bin Zhang (Food Chemistry, 2026)

A 13,100-year record of net primary productivity from subtropical China reveals shifting climatic and anthropogenic controls - Lin Zhao; Shanshan Meng; Zijian Liu; Tengwen Long; Zhiguo Rao; Haibin Wu (Anthropocene, 2026)

Characterization of a novel Era-homolog (AtERG1) in Arabidopsis that is essential for chloroplast development - Yi Lin; Shuangyuan Jia; Chenchen Zhang; Shanshan Chen; Han Xiang; Jiaqi Chen; Ying Yang; Jiawei Chen; Ming Li; Jinwen Liu (Journal of Plant Biochemistry and Biotechnology, 2026)

YAP/TEAD complex restricts H3K27ac deposition to suppress testosterone synthesis in adult Leydig cells - Zeyu Lin; Shanshan Luo; Mei Zheng; Zihang Lin; Lvjing Luo; Dini Zhang; Xiuli Lian; Xuanyi Wang; Shie Wang; Jiandong Sun (Histochemistry and Cell Biology, 2026)

Microbial niches and metabolism drive spatial heterogeneity of hydroxyapatite precipitation in aerobic granular sludge - Gonglei Wang; Fan Yang; Shanshan Xu; Dexin Lin; Rui Yang; Peng Yan; Youpeng Chen; Fang Fang; Jinsong Guo (Water Research, 2026)

Multi-objective sparrow search-based feature selection via weighted oversampling with intuitionistic fuzzy C-means for imbalanced classification - Lin Sun; Shanshan Si; Weiping Ding; Jiucheng Xu (Swarm and Evolutionary Computation, 2026)

Sea‐Level Rise Constrains the Carbon Permanence of Global Mangrove Restoration - Jincheng Wu; Zhe Zhao; Philippe Ciais; Shanshan Song; Chenyi Yuan; Guanghui Lin; Bertrand Guenet; Annemiek Stegehuis; Xiaoshan Zhu; Ruili Li; Ruikun Gou; Yuchen Meng; et al. (Global Change Biology, 2026)
Mangroves are characterized by high carbon sequestration rates, and future changes in mangrove biomass will be impacted by factors such as climate change, sea level rise, and management strategies. Here, we produce a map of present‐day global mangrove aboveground biomass (AGB) based on extensive field observations and satellite data, giving a global mangrove AGB of 1.76 Pg dry matter (DM). After accounting for potential growth to maturity, future changes in climatic and hydrological conditions, possible restoration strategies, and sea‐level rise, the global total mangrove AGB is projected to increase by 16.7% under the low‐warming scenario (Shared Socioeconomic Pathway 1 and Representative Concentration Pathway 2.6, SSP126) and decrease by 19.3% under the high‐warming scenario (SSP585) by 2100. Sea‐level rise encroaching upon the growth space of mangroves will cause a biomass loss of 41.6% in the high‐warming scenario, whereas restoration strategies would only increase AGB by 2.0%. Our study shows that sea‐level rise limits the potential of mangrove restoration to maintain carbon stocks, and regions less constrained by sea‐level rise offer greater potential for the long‐term permanence.

Post-storm fine-particle deposition and heavy-metal enrichment in a surface event layer of the northeastern Beibu Gulf after Super Typhoon Yagi - Haidong Li; Yunpeng Lin; Yunhai Li; Hengbo Wang; Shanshan Zhang; Hannv Zhang; Guicai Zhong; Jinlong Wang; Fanyu Lin (Frontiers in Marine Science, 2026)
Storm-generated surface deposits can preserve short-lived sedimentary and geochemical signals, but their interpretation requires careful distinction between event-layer contrasts and true pre–post storm changes. Here we examine the sedimentary and heavy-metal characteristics of a post-storm surface drape and the underlying reference sediment in the northeastern Beibu Gulf after Super Typhoon Yagi. Grain size, total organic carbon (TOC), aluminum (Al), and heavy metal concentrations were analyzed, and interlayer differences were evaluated using correlation analysis and a Surface–Subsurface Contrast Index (SSCI). Because sediment samples were collected 20–21 days after Typhoon Yagi and no directly observed pre-typhoon surface baseline was available, the observed differences are interpreted as post-event surface–subsurface contrasts rather than direct pre–post storm concentration changes. The surface drape is laterally persistent, finer grained, and enriched in TOC and Al, indicating that it primarily records post-storm settling of fine particles rather than deposition under peak storm energy. Most metals, including V, Cr, Co, Ni, Zn, Pb, Mn, and As, show higher concentrations in the surface drape than in the subsurface reference layer, with mean surface–subsurface contrasts of 35–61%, whereas Cu shows only a limited contrast and Cd remains broadly unchanged. V, Cr, Co, Ni, Zn, and Pb exhibit spatially coherent high-value zones in the surface drape, broadly consistent with the distribution of fine-grained and Al-rich sediments. These contrasts suggest that the post-storm surface drape preferentially preserved fine-grained, Al-rich, and organic-bearing particles that acted as metal carriers. Our results highlight that post-storm surface sediments in tropical–subtropical bays should be interpreted as event-layer archives of short-term sedimentary and geochemical reworking rather than as simple indicators of long-term background seabed conditions. These findings provide insight into how extreme storms may imprint short-term source-to-sink signals in coastal event deposits.

Changes in drug resistance trend of Klebsiella pneumoniae in a teaching hospital in Zhejiang Province, 2005 – 2023 - Yulu Duan; Min Shen; Weiwei Zhang; Junda Zhou; Yueyang Xiao; Shanshan Deng; Xu Jia; Lin Zhang (Next Research, 2026)

Gastric pH-induced liquid–liquid phase separation between lactoferrin and osteopontin protects against proteolysis and modulates intestinal uptake - Lan Liu; Chenming Lin; Meidan Zheng; Xinyue Tu; Yaming Yu; Zehan Song; Guoqiang Qi; Shanshan Li; Mingying Yang; Bo Lönnerdal; Yajun Shuai (Food Research International, 2026)

Associations between non-methane volatile organic compounds and cause-specific mortality across 14 major categories - Shengtao Wei; Ge Chen; Lan Chen; Zijun Yang; Fei Tian; Peng Hu; Kin Fai Ho; Shanshan Ran; Dashan Zheng; Hualiang Lin (Environmental Pollution, 2026)

Engineering selenium-doped carbon dots as a high-performance ECL emitter for dual-mode sensing of p53 in vitro and in living cells - Jingshuo Jiang; Jie Song; Yang Liu; Chong Wang; Shanshan Wu; Subin Wei; Shihan Lin; Chao Wang; Jing chen; Pengfei Wei; Ningning Wang (Chemical Engineering Journal, 2026)

A low-power and visualized varicose vein ablation surgery based on interventional optical fiber therapeutic probe - Fangzhou Jin; Yinsheng Lin; Yading Luo; Jian Han; Xu Yue; Wenwei Chen; Yongkang Zhang; Shanshan Guo; Xiaobing Niu; Jun Guo; Bai-Ou Guan; Chengzhi Li; et al. (Chemical Engineering Journal, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Exploring the potential of generative AI to complement multi-stakeholder landscape preference assessment - Jingya Lin; Chongzhi Chen; Tian Feng; Sigao Huo; Kexin Zhang; Baiyu Dong; Shanshan Xiang; Ke Wang; Lu Huang (Landscape and Urban Planning, 2026)

Exposure to polycyclic aromatic hydrocarbons during maternal pregnancy: Effects of DNA damage on neural tube defects in offspring - Xiaoqian Jia; Yingfeng Gao; Yuan Li; Ruiwei Xu; Lei Jin; Linlin Wang; Aiguo Ren; Le Zhang; Yali Zhang; Shanshan Lin; Jicheng Gong; Zhiwen Li (Journal of Hazardous Materials, 2026)

Stand age drives divergent microbial metabolic limitations and ecosystem multifunctionality between rhizosphere and bulk soils in subtropical Cryptomeria japonica plantations - Shanshan Huang; Yi Jian; Jing Li; Dengjie Zhou; Zhenfeng Xu; Bo Tan; Xinglei Cui; Tong Zhang; Lin Xu; Han Li; Li Zhang; Lixia Wang; et al. (Soil Ecology Letters, 2026)

Identification of marine algal blooms by SDGSAT-1 multispectral imagery - Shanshan Jiang; Rongda Guan; Qianguo Xing; Jie Li; Yingzhuo Hou; Wenjing Zhang; Lin Li; Maham Arif; Jinghu Li; Yunwei Tang (Remote Sensing of Environment, 2026)

Effects of low-level lead exposure on hematological parameters and the possible underlying mechanisms - Xiaojing Liao; Tao Lin; Zhaorui Zhang; Peng He; Haimei Wu; Xinyi Ouyang; Qianxi Li; Zihan Yu; Ziyan Zhang; Jiahui Wu; Yingxin Guo; Shanshan Wang; et al. (Environmental Pollution, 2026)

Effect of ivarmacitinib on swelling and tenderness in small and large joints and imaging changes in patients with moderate-to-severe RA: a post hoc analysis of a phase III clinical trial - Yuxiang Han; Meng Ding; Shaoxin Cui; Yu Tian; Yushu Yang; Xuying Liu; Lin Yang; Xiaoping Wang; Hongtao Jin; Huifang Guo; Haixue Dai; Shanshan Yin; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

The cNED framework: modeling core microbial communities and metabolic functions with SHAP-interpretable environmental thresholds in large rivers - Lunhui Lu; Xingqian Jian; Shanshan Lin; Zhe Li; Qiong Tang; Yan Xiao; Yuanyuan Zhang; Dianchang Wang (Water Research, 2026)

Preserving the functional integrity of BiP1 is essential for rice storage protein export from the endoplasmic reticulum - Wenkun Yang; Tian Pan; Fan Wang; Yun Zhu; Kunneng Zhou; Binglei Zhang; Gexing Wan; Yu Chen; Yu Zhang; Xiejun Sun; Cailin Lei; Jie Wang; et al. (Plant Science, 2026)

Selective recover of bismuth by amide extractant from chloride leaching of lead anode slime and the mechanism - Jinhua Bai; Manxing Huo; Lin He; Shiwei Wang; Qifeng Wei; Xiulian Ren; Shanshan Wang (Journal of Environmental Chemical Engineering, 2026)

Deciphering the clearance efficacy on the soil of slag stockpiles via lead isotopic signatures - Zhenghua Tao; Lina Zhang; Lin Jia; Ke Pan; Rongfei Wei; Shanshan Chen; Xiaoying Zhu; Ningning Wang; Danhua Yang; Tianxiang Xia (Journal of Environmental Management, 2026)

Enhancement of MOF loading on fibrous membranes via construction of hierarchical porous structure for efficient uranium adsorption in aqueous solutions - Yiting Lin; Yuhan Zhang; Zhaoxuan Duan; Yufei Zou; Shanshan Li; Zhenbo Cao (Journal of Environmental Chemical Engineering, 2026)

Transport and retention mechanism of CdS nanoparticles in layered heterogeneous porous media: Coupled regulation of interfacial heterogeneity and ionic strength - Xiangru Liu; Xin Yang; Hongfei Du; Xiaoyang Yue; Shanshan Lin (Journal of Environmental Management, 2026)

Multi-membrane integrated process enables efficient electrodialytic separation of alkaloids from aqueous extract of Caulis sinomenii - Lanlan Zhang; Xixi Ma; Tingting Xu; Shanshan Liu; Luna Chen; Jiaming Ji; Jinfeng He; Li Sun; Xiaocheng Lin; Chuanrun Li; Haiyang Yan (Desalination, 2026)

Multi-strategy engineering of Saccharomyces cerevisiae for enhanced β-ionone biosynthesis - Ping Lin; Shanshan Xu; Jian Chen; Juan Zhang; Zheng Peng (Chemical Engineering Journal, 2026)

Posttranslational regulation of TOR kinase activity controls resource allocation between plant growth and immunity in Arabidopsis - Jianwei Li; Ran Wang; Chenying Li; Xijie Guo; Qinghong Li; Zhixuan Wu; Shanshan Zeng; Fan Qi; Yuchen Wang; Zhiyi Jia; Weiwei Yu; Zeming Huang; et al. (Molecular Plant, 2026)

Spatiotemporal evolution of trade-off/synergy relationships and bundles in ecosystem services in Fujian, China: An integrated PLUS-InVEST-SOM framework - Zhihui Lin; Zhu He; Chenjie Ye; Yanan Li; Haolan Liu; Shanshan Ding; Xiaoyang Qiao; Jiayu Xiong; Jiakang Huang; Xisheng Hu; Jian Li (Journal of Cleaner Production, 2026)

Significant suppression of sulfur–containing organic aerosols by emission controls during the Hangzhou Asian Games - Jintian Zhang; Lei Liu; Jianxiong Rong; Lin Du; Zechen Yu; Shanshan Tang (Journal of Environmental Sciences, 2026)

Honeycomb electrode-based triboelectric nanogenerator for deep learning-derived bimodal human-machine interaction systems - Lingxiao Li; Wandi Chen; Liangjie Liu; Yibin Lin; Yanmin Guo; Shanshan Jiang; Lei Sun; Yongai Zhang; Tailiang Guo; Chaoxing Wu; Xiongtu Zhou (Chemical Engineering Journal, 2026)

Superhydrophilic hierarchically porous all biomass membranes for enhanced anti-fouling and filtration performance - Zhenhao Lin; Xin Liu; Kehao Huang; Jiwen Luo; Shanshan Li; Xiaoying Wang (Chemical Engineering Journal, 2026)

Mechanistic Links Between Suspended Sediment Dynamics and Metal Partitioning Under Tidal Forcing: A Case Study of Quanzhou Bay - Yanbin Fan; Yunhai Li; Yunpeng Lin; Shangshang Yang; Zhijie Chen; Xiang Cao; Chenyang Wang; Shanshan Zhang; Jinzeng Jiang; Mingyang Jiang; Kaichao Wan (Journal of Marine Science and Engineering, 2026)
The coupling of physical transport and phase-transfer processes represents a fundamental mechanism governing metal cycling in estuarine systems under tidal oscillations. Taking Quanzhou Bay as a model system, we conducted continuous observations and sample collection at the river channel (Q1), the turbidity maximum zone (Q2), and the outer bay channel (Q3). The metals (Al, Ti, Ba, Cu, Mn, and Zn) were measured by ICP-MS to systematically investigate the distribution, transport, and inter-media transfer across multiple water layers under varying estuarine processes. Our findings demonstrate that particulate metal concentrations in Quanzhou Bay exhibit strong synchrony with suspended sediment concentrations (SSC) over tidal cycles, displaying a distinct sediment-following pattern controlled by alternating end members. Particulate metal fluxes during flood and ebb-tides generally followed the hierarchy Q1 > Q2 >> Q3. Notably, stations Q1 and Q2 were dominated by flood-tide fluxes with net transport directed landward, whereas Q3 was characterized by ebb tide dominance with net flux directed seaward—revealing a spatial division of labor between “inner bay retention/reallocation” and “outer bay channel export”. In contrast, dissolved metals exhibited marked element-specific responses to tidal forcing: Al and Ti increased during flood tides at stations Q1 and Q2, while Ba and Cu showed opposite trends, and Mn and Zn displayed more conservative behavior. Concurrently, solid/liquid partition coefficient (logKd) values for Al, Ti and Ba, Cu exhibited inverse patterns over tidal cycles, suggesting divergent adsorption–desorption regulation under identical hydrodynamic conditions that drives differential phase-transfer dynamics. These disparities likely reflect intrinsic chemical properties and source variations among the elements. This study elucidates, at the tidal timescale, the coupled processes of “alternating end-member control—estuarine filter modulation—concurrent channelized export and inner bay retention” in Quanzhou Bay, providing critical process-level insights for metal flux quantification and bay pollution remediation initiatives in an ecological restoration project.

Short-term and long-term effects of outdoor artificial light at night on reproductive hormones among infertile women from a preconception cohort study - Wenbin Fang; Cun Huang; Ying Tang; Mengdie Li; Yaning Sun; Yanlan Tang; Yinyin Chen; Yawen Cao; Jiqi Fang; Kunjing He; Jing Shen; Zhiyuan Huang; et al. (International Journal of Biometeorology, 2026)

Associations of air pollution and genetic risk and their interaction with risk of Alzheimer’s disease: identification of risk loci and potential biological pathways - Shanshan Ran; Jingyi Zhang; Miao Cai; Lan Chen; Zhengmin Qian; Fei Tian; Gan Wu; Ri’enna Boyd; Stephen Edward McMillin; Huai-cai Zeng; Yin Yang; Hualiang Lin (GeroScience, 2026)

Cross-scale synergistic detoxification mechanisms of electric field in alleviating the inhibitory effects of oxytetracycline on anammox consortia - Hongfei Du; Xinlong Wang; Xiangru Liu; Xin Yang; Xiaoyang Yue; Shanshan Lin; Dandan Zhou (Water Research, 2026)

Exploring the role of VAV2 rare variants in primary open-angle glaucoma: genetic insights and pathophysiological mechanisms - Runze Li; Yuhong Chen; Shanshan Zhang; Lin Ye; Huaping Tian; Zheng Li; Wentao Wang; Hongjing Li; Ruilin Liao; Haojue Xu; Junlan Chuan; Chao Qu; et al. (Science China Life Sciences, 2026)

Organic phosphorus strategy combining target crops and the environment to advance food production and reduce agricultural phosphorus loss - Zheng Li; Shanshan Jiang; Xuanjing Chen; Yubin Zhang; Ning Cao; Xinglin Du; Liyuan Hou; Yi Zhang; Xiaoli Wang; Dayong Guo; Xinping Chen; Lin Ma; et al. (Agriculture, Ecosystems & Environment, 2026)

Transcriptomic and Metabolomic Responses to Growth Differences in Litopenaeus vannamei Infected with Enterocytozoon hepatopenaei - Shanshan Li; Yong Wu; Jiaqi Jin; Bo Wu; Chenxi Zhao; Zhihua Lin; Minhai Liu; Zhilan Peng (Fishes, 2025)
Litopenaeus vannamei, a widely cultivated aquatic species worldwide, has its growth status intrinsically tied to the economic profitability of the aquaculture industry. However, infection by the microspondian parasite Enterocytozoon hepatopenaei (EHP) has emerged as a pivotal threat to the healthy growth of these shrimp. Through transcriptome sequencing, this study identified substantial alterations in gene expression patterns related to growth regulation, immune system activation, and energy metabolism regulation. Specifically, in L. vannamei shrimp exhibiting normal growth, the elevated expression of genes such as CYP450, PPAF, FASN and ACSBG2 serves as molecular indicators of their growth superiority and resistance to parasitic infection. Furthermore, metabolome analysis revealed distinct changes in lipid and nucleotide metabolic pathways, offering valuable insights into the metabolic disruptions caused by infection. The integrated analysis of transcriptome and metabolome data indicated a notable positive correlation between the differentially expressed genes TPi and ALF-like, and the metabolites acetyl-L-carnitine and citric acid. This suggests potential synergistic mechanisms in regulating energy metabolism and immune responses against EHP infection. These findings enhance our comprehension of EHP infection mechanisms and establish a scientific groundwork for developing more precise and efficacious prevention and control strategies, ultimately promoting the healthy growth of L. vannamei and ensuring the sustainable development of the aquaculture industry.

Deacetylation mediated non-covalent assembly for regulating sol-gel behavior of chitin-NaOH solution - Xinghuan Lin; Zhiqiang Liu; Ming Lei; Jiaying Xie; Hanji Chen; Shanshan Li; Bo Duan (Carbohydrate Polymers, 2025)

Pregnant PM2.5 exposure promotes uterine contractility via miR-200a-PGR-oxytocin signaling pathway leading to preterm birth - Jingyi Zhang; Shanshan Ran; Shengtao Wei; Zijun Yang; Huaicai Zeng; Guang Jia; Zhangjian Chen; Lan Chen; Fei Tian; Ge Chen; Zilong Zhang; Hualiang Lin (Atmospheric Environment, 2025)

Effects of MS-222 on the physiological and biochemical response, histomorphology, gut microbiota, and flesh quality in largemouth bass (Micropterus salmoides) - Ping Gao; Rimeng Chen; ShanShan Lin; Haodong Yu; Xuezhen Zhang (Fish Physiology and Biochemistry, 2025)

Self-repair mechanisms of spiking neuron–astrocyte networks in working memory under diverse injury conditions - Bingyi Mo; Xiaoqian Liu; Lin Li; Shanshan Cheng; Yuan Zhu; Ming Yi; Lulu Lu (Cognitive Neurodynamics, 2025)

Ultrasound-induced modifications in structure, antioxidant activity and functionality of whey protein isolate-propolis polyphenol conjugates - Shanshan Li; Shiqin Peng; Lin Wei; Jingyan Li; Yuanyuan Lu; Xiaobin Ma; Fuliang Hu (Food Chemistry, 2025)

Food-derived bioactive peptides: health benefits, structure–activity relationships, and translational prospects - Hongda Chen; Jiabei Sun; Haolie Fang; Yuanyuan Lin; Han Wu; Dongqiang Lin; Zhijian Yang; Quan Zhou; Bingxiang Zhao; Tianhua Zhou; Jianping Wu; Shanshan Li; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

Halogenated flame retardants in the sediments of the lower Great Lakes and region-wide discoveries - Tian Lin; Shanshan Zhou; Huan He; Jiehong Guo; Neil C. Sturchio; Karl J. Rockne; John P. Giesy; An Li (Journal of Hazardous Materials, 2025)

The physiological effects of intrinsic and isolated arabinoxylans on human immunometabolic response: A systematic review and meta-analysis - Shanshan Jiang; Chenxi Cai; Edward C. Deehan; Junyu Chen; Changcan Feng; Mingyue Yang; Zhongming Weng; Jiahui Long; Jiaxuan Xie; Shan Lin; Guiling Li; Jian Li; et al. (Food Research International, 2025)

Tea aroma retention strategies using tea polysaccharide conjugates: Insights from the yellowing process - Anan Xu; Meng Tao; Zheng Tu; Shanshan Wang; Yanyan Cao; Lin Chen; Zhengquan Liu (Food Chemistry, 2025)

Surface oxygen vacancies-engineered spherical bismuth molybdate: Enhanced visible-light-driven photocatalytic activity for selective oxidation of benzyl alcohol under ambient conditions - Ying-Ying Xu; Wen-Yu Luo; Fei Wen; Yanfei Xu; Zhuo Li; Shanshan Liu; Ze-Long Sun; Xiaoxun Ma; Mingyue Ding; Lin-Yu Jiao (Chemical Engineering Journal, 2025)

Mangrove above- and belowground traits co-vary but are not fully aligned with the economic spectrum during the development of Bruguiera sexangula trees in Hainan, China - Shanshan Song; Marie Arnaud; Cornelia Rumpel; Guanghui Lin (Plant and Soil, 2025)

Trps1 targets Scarb1 to regulate cholesterol acquisition in mouse Leydig cells - Xiuli Lian; Zihang Lin; Weitao Hu; Zhangting Chen; Shanshan Luo; Shumin Liao; Yue Liu; Shie Wang; Jiandong Sun (Reproductive Biology, 2025)

Biodegradable microplastics exacerbate the risk of antibiotic resistance genes pollution in agricultural soils - Dan Zhang; Jianbin Sun; Shuang Peng; Yiming Wang; Xiangui Lin; Shanshan Wang (Journal of Hazardous Materials, 2025)

Donor-acceptor engineered heptazine heterostructures with cascade nanozyme activity: A multidimensional signal-amplified biosensor for envelope glycoprotein E2 monitoring - Yanjie Chen; Lihong Gao; Shupei Zhang; Shanshan Yan; Xuejun Zhou; Feng Lin; Hong Dai (Chemical Engineering Journal, 2025)

Genome-Wide Identification and Expression Analysis of the Basic Helix-Loop-Helix (bHLH) Transcription Factor Family in Gastrodia elata - Shanshan Lan; Xin Lin; Maoqiong Wei; Guangheng Feng; Hongcheng Liu; Jinliang Shao; Xinyu Li; Zeli Chen; Zhenhuan Liu (Plant Molecular Biology Reporter, 2025)

In vitro and in vivo evidence on the association of pregnant PM2.5 exposure with preterm birth and potential role of placental miRNA-21 regulating TLR4/NF-κB and activating NLRP3 inflammasome - Shanshan Ran; Wenxue Li; Zijun Yang; Jingyi Zhang; Zhangjian Chen; Guang Jia; Qingmei Lin; Huai-cai Zeng; Yin Yang; Zilong Zhang; Yonggui Gao; Lan Chen; et al. (Journal of Hazardous Materials, 2025)

Genetic and metabolic signatures of blooming-stage tea flowers in novel albino cultivars: Implications for functional food development - Shanshan Zeng; Xiansheng Liao; Zheng Liu; Feng Liu; Wenjing Gui; Weiwei Ren; Hongzheng Lin; Yucheng Zheng; Naixing Ye (Food Bioscience, 2025)

Ecological connectivity between mangroves and seagrasses increases sediment blue carbon storage - Xinao Guo; Shanshan Song; Lieyi Chen; Conghe Zhang; Shengbin Ye; Yali Ding; Ruikun Gou; Xiaoping Huang; Shuguo Lv; Neil Saintilan; Daniel A. Friess; Guanghui Lin (Estuarine, Coastal and Shelf Science, 2025)

Changes of food-cue processing in major depressive disorder patients with decreased appetite: An event-related potential study - Shanshan Lin; Yiwei Du; Yujie Xia; Cai Nan; Shenhong Weng; Lin Zhou; Ling Xiao; Gaohua Wang (Appetite, 2025)

Pilot-scale application on Fe-C coupled natural zeolite for total nitrogen removal in low C/N black odorous water - Hongyang Yu; Qiheng Han; Tao Li; Shanshan Lin (Journal of Environmental Chemical Engineering, 2025)

Corrigendum to “Alterations in the nutrient composition, muscle quality, and proteomics of two Sepiidae species (Sepiella maindroni and Sepia esculenta) during storage” [Food Bioscience, 62, 105440] - Jiang Shanshan; Lin Huimin (Food Bioscience, 2025)

A zwitterionic polymer binder Integrating multiple dynamic interactions enables High-Performance Lithium − Sulfur batteries - Xiangyu Lin; Yong Wen; Danna Ma; Jie Li; Ziming Zhu; Shanshan Wang; He Liu; Xu Xu; Xujuan Huang (Chemical Engineering Journal, 2025)

Covalent and non-covalent cross-linked based polymer binders for high-sulfur-loading lithium-sulfur batteries - Danna Ma; Yong Wen; Xiangyu Lin; Jie Li; Ziming Zhu; Shanshan Wang; He Liu; Xu Xu (Chemical Engineering Journal, 2025)

Divergent responses of abundant and rare bacterial communities to environmental variables in highly urbanized coastal regions: N-NO2- mediates the community assembly and co-occurrence networks - Shanshan Ma; Lin Zhang; Longjie Zhang; Shuai Zhang; Yiyi Zhu; Jun Wang; Keshu Zou (Journal of Environmental Management, 2025)

Efficiency of iron–carbon microelectrolysis in the treatment of nitrate and phosphate in printed circuit board production wastewater: The critical role of Cu2+ - Hongyang Yu; Xinlong Wang; Xiangru Liu; Dongyu Peng; Huina Liu; Xin Yang; Shanshan Lin (Journal of Environmental Chemical Engineering, 2025)

Identification of Dendrobium officinale species and authentication of commercial products by DNA barcoding and high-resolution melting analysis - Zhilong He; Zhao Yang; Cui Dong; Shanshan Yan; Jing Lin; Hexigeduleng Bao; Fan Tang; Leilei Zhang; Cheng Zhu; Yan Hu; Yanfei Ding (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Multi-Omics Exploration of Obesity Biomarkers in Sedentary and Weight Loss Cohorts - Hui Wang; Yixiao Zhuang; Rong Hua; Ting Yao; Kaiqing Lin; Yitao Zhang; Rui Huang; Ruwen Wang; Shanshan Guo; Qiwei Shen; Yikai Shao; Wei Wu; et al. (Phenomics, 2025)

LncRNAs: expanding horizons in drug development and disease treatment - Zhizhuo Wang; Junfeng Wang; Wenfei Wu; Chengyu Shi; Ying Wang; Yu Chen; Fangzhou Liu; Shanshan Xie; Aifu Lin (Science Bulletin, 2025)

Liquid-liquid phase separation of TRAF6 promotes anti-TB immunity - Yongjia Duan; Yuanna Cheng; Mingtong Ma; Liru Li; Shanshan Liu; Liru Guan; Jie Wang; Hongjie Liu; Xiaochen Huang; Jianxia Chen; Hua Yang; Baoxue Ge; et al. (Science Bulletin, 2025)

Unintentional emissions of polychlorinated naphthalenes in China: Sources, composition, and historical trends - Ye Huang; Lin Huang; Ying Li; Nazupar Sidikjan; Yunshan Zhang; Yan Chen; Yangmin Chen; Ye Li; Wei Du; Long Chen; Yan Wu; Shanshan Zhang; et al. (Journal of Environmental Sciences, 2025)

OsPAD1, encoding a non-specific lipid transfer protein, is required for rice pollen aperture formation - Qiming Wang; Yunlu Tian; Keyi Chen; Shanshan Zhu; Yehui Xiong; Chaolong Wang; Xiaowen Yu; Wenting Bai; Hai Zheng; Shimin You; Yang Hu; Dekun Lei; et al. (Plant Molecular Biology, 2025)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Urban surface-emitted longwave radiation estimation from high spatial resolution thermal infrared images using a hybrid method - Songyi Lin; Huazhong Ren; Rongyuan Liu; Jinxiang Li; Shanshan Chen; Yuanjian Teng; Wenjie Fan; Baozhen Wang; Yu Liu (Remote Sensing of Environment, 2024)

Variation profiles, formation mechanisms, and emission risks of brominated flame retardant compounds during cement kiln co-processing of hexabromocyclododecane-containing waste - Xin Li; Yahui Liu; Bingcheng Lin; Guohua Zhu; Jian Wang; Xiao Wang; Yueyao Yang; Shanshan Zhang; Guorui Liu; Rong Jin; Minghui Zheng (Journal of Hazardous Materials, 2024)

Enhancement of the reactivation process of long-term starved anammox granular sludge with gravel balls: Microbial succession and metabolic impact - Xinlong Wang; Qiheng Han; Hongyang Yu; Shanshan Lin (Environmental Research, 2024)

Signature and function of plasma exosome-derived circular RNAs in patients with hypertensive intracerebral hemorrhage - Kejie Chen; Xiaoyuan Cheng; Shanshan Yuan; Yang Sun; Junli Hao; Quandan Tan; Yapeng Lin; Shuping Li; Jie Yang (Molecular Genetics and Genomics, 2024)

First report of zedoary leaf blight caused by Neopestalotiopsis asiatica on Curcuma phaeocaulis in Guangxi, China - Shanshan Li; Meimei Long; Yaqi Luo; Liguo Huang; Qiangyi Cheng; Xianchao Sun; Lin He; Guanhua Ma (Physiological and Molecular Plant Pathology, 2024)

Cadmium contamination in sediments from a mangrove wetland: Insights from lead isotopes - Zhenghua Tao; Tianxiang Xia; Fengyuan Chen; Lina Zhang; Rongfei Wei; Shanshan Chen; Lin Jia; Wenlu Lan; Ke Pan (Journal of Hazardous Materials, 2024)

Influence of perfluorooctanoic acid on alkaline anaerobic fermentation of waste activated sludge: Perspective from volatile fatty acids production and sludge reduction - Zhilin Zhao; Xiaoying Zheng; Shanshan Yang; Haidong He; Zongshuo Han; Wenfei Li; Tao Lin; Hang Xu (Journal of Environmental Management, 2024)

Fabrication of Fe-Ti heteroatom-based metal-organic framework with vantage defects for high-efficient arsenic removal from water - Shanshan Shang; Xinyu Chen; Chao Yang; Ying Zhou; Kaimin Shih; Lin Lin; Xiao-yan Li (Chemical Engineering Journal, 2024)

Unveiling the versatile performance of transition metal sulfides in peroxymonosulfate activation - Zhifang Zhao; Lin Lin; Shanshan Liu; Yiqian Chen; Sanford V. Daniels; Zijian Xu; Zhenhua Chen; Haitao Li; Yanqing Wu; Lingling Guo; Qiteng Zheng; Zhenhua Duan; et al. (Chemical Engineering Journal, 2024)

Contrasting aerosol effects on shallow and deep convections during the Mei-yu season in China - Lin Liu; Chunze Lin; Chunguang Cui; Chendi Wang; Hao Yang; Shanshan Li (Atmospheric Research, 2024)

Analysis of the Spatio-Temporal Characteristics of Winter Surface Urban Heat Island: A Case Study in Beijing, China - Shanshan Lu; Fujiang Liu; Yunshuang Ye; Jiayu Tang; Peng Li; Weihua Lin; Yan Guo; Ruqiang Ma; Jun Wang (Journal of Earth Science, 2024)

Photochemical transformation of liquid crystal monomers in simulated environmental media: Kinetics, mechanism, toxicity variation and QSAR modeling - Yandong Yang; Xiangkun Jiang; Yi Yang; Jia Wang; Yahui Zhao; Shanshan Lin; Jiao Qu; Christopher J. Martyniuk; Yuanhui Zhao; Chao Li (Water Research, 2024)

Effects of the quorum sensing related luxS gene and lsr operon on Klebsiella michiganensis resisting copper stress - Ya Gao; Dongyu Peng; Xinlong Wang; Shanshan Lin (Environmental Research, 2024)

Application of C30 tetracyclic polyprenoids as effective biomarker in oil-to source rock correlation in the Zhu III depression, Zhujiangkou Basin, northern South China - Lei Lan; Youchuan Li; Shuchun Yang; Yang Ouyang; Wenjing Ding; Qing Lin; Shanshan Zhou (Acta Oceanologica Sinica, 2024)

Characteristics and degradation mechanisms of polychlorinated naphthalenes in surface soil in Yangtze River Delta, China - Zherui Zhang; Guohua Zhu; Yahui Liu; Xin Zhou; Bingcheng Lin; Ziyuan Qi; Shanshan Zhang; Yueyao Yang; Xin Li; Rong Jin; Minghui Zheng (Chemosphere, 2024)

Co-hydrothermal carbonization of municipal sludge and agricultural waste to reduce plant growth inhibition by aqueous phase products: Molecular level analysis of organic matter - Guangchun Shan; Weiguang Li; Jie Liu; Shanshan Bao; Zhenling Li; Shuncai Wang; Lin Zhu; Beidou Xi; Wenbing Tan (Science of The Total Environment, 2024)

Effect of a collagen peptide–fish oil high internal phase emulsion on the printability and gelation of 3D-printed surimi gel inks - Shanshan Lu; Zhisheng Pei; Quanhong Lu; Qian Li; Yanfu He; Aiguo Feng; Zhongyuan Liu; Changfeng Xue; Jianhua Liu; Xiangdong Lin; Yongcheng Li; Chuan Li (Food Chemistry, 2024)

Biochar with enhanced performance prepared based on “graphite-structure regulation” conjecture designed to effectively control water pollution - Bolun Zhang; Yiping Jin; Jiacheng Lin; Ziyu Guo; Guang Chen; Yingjie Su; Xiaoxiao Yu; Shanshan Tang; Siji Chen; Jian Li (Science of The Total Environment, 2024)

OsPRMT6a-mediated arginine methylation of OsJAZ1 regulates jasmonate signaling and spikelet development in rice - Kun Dong; Fuqing Wu; Siqi Cheng; Shuai Li; Feng Zhang; Xinxin Xing; Xin Jin; Sheng Luo; Miao Feng; Rong Miao; Yanqi Chang; Shuang Zhang; et al. (Molecular Plant, 2024)

Effect of aqueous phase from hydrothermal carbonization of sewage sludge on heavy metals and heavy metal resistance genes during chicken manure composting - Guangchun Shan; Xiaoshu Wei; Weiguang Li; Jie Liu; Shanshan Bao; Shuncai Wang; Lin Zhu; Beidou Xi; Wenbing Tan (Journal of Hazardous Materials, 2024)

Development and comprehensive SBSE-GC/Q-TOF-MS analysis optimization, comparison, and evaluation of different mulberry varieties volatile flavor - Di Ma; Tianbao Lin; Huiyu Zhao; Yougui Li; Xinquan Wang; Shanshan Di; Zhenzhen Liu; Mingqi Liu; Peipei Qi; Suling Zhang; Rui Jiao (Food Chemistry, 2024)

Characterization of a novel recombinant NADC30‑like porcine reproductive and respiratory syndrome virus in Shanxi Province, China - Jianle Ren; Shanshan Tan; Xinxin Chen; Xizhen Wang; Yiting Lin; Yi Jin; Sheng Niu; Ying Wang; Xiaolong Gao; Libin Liang; Junping Li; Yujun Zhao; et al. (Veterinary Research Communications, 2024)

Linarin Ameliorates Restenosis After Vascular Injury in Type 2 Diabetes Mellitus via Regulating ADAM10-Mediated Notch Signaling Pathway - Aihua Jiang; Lin Liu; Jianping Wang; Yinglan Liu; Shanshan Deng; Tao Jiang (Cardiovascular Toxicology, 2024)

CO2 fluxes contrast between aquaculture ponds and mangrove forests and its implications for coastal wetland rehabilitation in Leizhou Peninsula, China - Ruikun Gou; Jianxiang Feng; Haichao Zhou; Tao Lang; Jiayu Zhao; Lidong Mo; Shanshan Song; Guanghui Lin (Agriculture, Ecosystems & Environment, 2024)

Household air pollution and attributable burden of disease in rural China: A literature review and a modelling study - Junling Yang; Zhi Lin; Shanshan Shi (Journal of Hazardous Materials, 2024)

Energy-efficient bubble aeration guided by bubble dynamics model: From bubble formation at submerged orifice to oxygen utilization during uprising - Zhen Chen; Jiaao Yu; Yang Huo; Jiancong Liu; Dan Xiao; Lipeng He; Shanshan Lin; Wei Fan; Mingxin Huo (Journal of Cleaner Production, 2024)

Exercise-induced microbial changes in preventing type 2 diabetes - Ting Yao; Hui Wang; Kaiqing Lin; Ruwen Wang; Shanshan Guo; Peijie Chen; Hao Wu; Tiemin Liu; Ru Wang (Science China Life Sciences, 2024)

Single-cell profile reveals the landscape of cardiac immunity and identifies a cardio-protective Ym-1hi neutrophil in myocardial ischemia–reperfusion injury - Yalan Dong; Zhenyu Kang; Zili Zhang; Yongqiang Zhang; Haifeng Zhou; Yanfei Liu; Xinxin Shuai; Junyi Li; Liangqingqing Yin; Xunxun Wang; Yan Ma; Heng Fan; et al. (Science Bulletin, 2024)

A hybrid system for Nickel ions removal from synthesized wastewater using adsorption assisted with electrocoagulation - Jean Claude Nizeyimana; Pamphile Ndagijimana; Junaid Khan; Liu Xiangru; Gratien Twagirayezu; Habasi Patrick Manzi; Olivier Irumva; Chang-Ping Yu; Anyi Hu; Shanshan Lin (Environmental Science and Pollution Research, 2024)

The photo- and microbial degradation kinetics and pathways of sulfadoxine in seawater elucidated by liquid chromatography coupled with time-of-flight mass spectrometry - Guowen Tang; Yuling Chen; Shanshan Lin; Xiaolin Li (Chemosphere, 2024)

Novel insights into aerobic 17β-estradiol degradation by enriched microbial communities from mangrove sediments - Shan Zhang; Xueying Ye; Xianbin Lin; Xiangwei Zeng; Shanshan Meng; Wenqi Luo; Fei Yu; Tao Peng; Tongwang Huang; Jin Li; Zhong Hu (Journal of Hazardous Materials, 2024)

Exosome-transmitted FOSL1 from cancer-associated fibroblasts drives colorectal cancer stemness and chemo-resistance through transcriptionally activating ITGB4 - Shanshan Lin; Bo Zhu (Molecular and Cellular Biochemistry, 2024)

Genome-wide identification and functional analysis of the cellulose synthase-like gene superfamily in common oat (Avena sativa L.) - Shanshan Zhang; Haibin Hu; Shumin Cui; Lin Yan; Bing Wu; Shanjun Wei (Phytochemistry, 2024)

The application of nanopore targeted sequencing for pathogen diagnosis in bronchoalveolar lavage fluid of patients with pneumonia: a prospective multicenter study - Qinqing Lin; Yake Yao; Xi Li; Shanshan Zhang; Huimin Guo; Xiaolong Ma; Wenyu Chen; Chuhui Ru; Limin Wang; Bin Wang; Qiang Ma; Junfei Zhu; et al. (Infectious Diseases, 2024)

Single-Cell Mapping of Brain Myeloid Cell Subsets Reveals Key Transcriptomic Changes Favoring Neuroplasticity after Ischemic Stroke - Fangxi Liu; Xi Cheng; Chuansheng Zhao; Xiaoqian Zhang; Chang Liu; Shanshan Zhong; Zhouyang Liu; Xinyu Lin; Wei Qiu; Xiuchun Zhang (Neuroscience Bulletin, 2024)

Metabolomics reveals that chronic restraint stress alleviates carbon tetrachloride-induced hepatic fibrosis through the INSR/PI3K/AKT/AMPK pathway - Shanshan Zhang; Binjie Liu; Lan Huang; Rong Zhang; Lin An; Zhongqiu Liu (Journal of Molecular Medicine, 2024)

Building a predictive model for hypertension related to environmental chemicals using machine learning - Shanshan Liu; Lin Lu; Fei Wang; Bingqing Han; Lei Ou; Xiangyang Gao; Yi Luo; Wenjing Huo; Qiang Zeng (Environmental Science and Pollution Research, 2023)

Dynamic response of root-associated fungal community structure to nitrogen and phosphorus additions in a subtropical forest - Shanshan Liu; Hao Yang; Luhong Zhou; Sheng-Sheng Jin; Lin Xie; Chengfang Lin; Ji-Zheng He; Yong Zheng (Pedobiologia, 2023)

Polysaccharide from walnut green husk alleviates liver inflammation and gluconeogenesis dysfunction by altering gut microbiota in ochratoxin A-induced mice - Yang Yang; Linjie Lv; Shanshan Shi; Gaofeng Cai; Lin Yu; Shuwen Xu; Tianyu Zhu; Xinyue Su; Ningning Mao; Yue Zhang; Song Peng; Jin He; et al. (Carbohydrate Polymers, 2023)

Macrogenomic analysis of the effects of aqueous-phase from hydrothermal carbonation of sewage sludge on nitrogen metabolism pathways and associated bacterial communities during composting - Guangchun Shan; Weiguang Li; Jie Liu; Wenbing Tan; Shanshan Bao; Shuncai Wang; Lin Zhu; Xinhao Hu; Beidou Xi (Bioresource Technology, 2023)

Removal of Nitrate from Wastewater by Nanoscale Zero-Valent Iron Synthesized from Polyhydroxy Alcohols - Huina Liu; Hongyang Yu; Yifeng Wu; Dongyu Peng; Shanshan Lin (Water, Air, & Soil Pollution, 2023)

Temporal variations of carbon and water fluxes in a subtropical mangrove forest: Insights from a decade-long eddy covariance measurement - Ruikun Gou; Nina Buchmann; Jinshu Chi; Yunpeng Luo; Lidong Mo; Ankit Shekhar; Iris Feigenwinter; Lukas Hörtnagl; Weizhi Lu; Xiaowei Cui; Yuchen Meng; Shanshan Song; et al. (Agricultural and Forest Meteorology, 2023)

Low contributions of dimethyl sulfide (DMS) chemistry to atmospheric aerosols over the high Arctic Ocean - Miming Zhang; Jinpei Yan; Qi Lin; Keyhong Park; Shuhui Zhao; Suqing Xu; Shanshan Wang (Atmospheric Environment, 2023)

Packed OV-SnO2-Sb bead-electrodes for enhanced electrocatalytic oxidation of micropollutants in water - Chao Yang; Lin Lin; Shanshan Shang; Shengshou Ma; Feiyun Sun; Kaimin Shih; Xiao-yan Li (Water Research, 2023)

Ambient air pollution associated with incident asthma, subsequent cardiovascular disease and death: A trajectory analysis of a national cohort - Xiaojie Wang; Shanshan Ran; Hui Xia; Hui Shi; Gan Wu; Zilong Zhang; Chongjian Wang; Miao Cai; Junguo Zhang; Hualiang Lin (Journal of Hazardous Materials, 2023)

Extrinsic compensation on separation performance of layer-by-layer nanofiltration membranes - Shanshan Xu; Rongrong He; Jiarui Chen; Juan Luo; Hao Chen; Shihong Lin; Yue-Biao Zhang; Tao He (Desalination, 2023)

Causal relationships between chronotype and risk of multiple cancers by using longitudinal data and Mendelian randomization analysis - Shanshan Tian; Longtao Huangfu; Sizhi Ai; Junwei Zheng; Le Shi; Wei Yan; Ximei Zhu; Qianwen Wang; Jiahui Deng; Yanping Bao; Suhua Chang; Lin Lu (Science China Life Sciences, 2023)

Astringin protects LPS-induced toxicity by suppressing oxidative stress and inflammation via suppression of PI3K/AKT/NF-κB pathway for pediatric acute lung injury - Ling Wang; Shanshan Jiang; Xiaoxiao Li; Tingting Lin; Tao Qin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Joint Return Value Estimation of Significant Wave Heights and Wind Speeds with Bivariate Copulas - Shanshan Tao; Sheng Dong; Yifan Lin; Carlos Guedes Soares (Journal of Ocean University of China, 2023)

A landfill serves as a critical source of microplastic pollution and harbors diverse plastic biodegradation microbial species and enzymes: Study in large-scale landfills, China - Xiaoxing Lin; Shanshan Zhang; Shu Yang; Rui Zhang; Xianyang Shi; Liyan Song (Journal of Hazardous Materials, 2023)

Effect of the aqueous phase from the hydrothermal carbonization of sewage sludge as a moisture regulator on nitrogen retention and humification during chicken manure composting - Guangchun Shan; Weiguang Li; Wenbing Tan; Shanshan Bao; Jie Liu; Shuncai Wang; Lin Zhu; Li Chen; Beidou Xi (Chemical Engineering Journal, 2023)

Ratiometric SERS imaging for indication of peroxynitrite fluctuations in diabetic wound healing process - Hui Chen; Shanshan Lin; Dianqi Zhang; Yanlong Xing; Fabiao Yu; Rui Wang (Chemical Engineering Journal, 2023)

mRNA sequencing and CyTOF analysis revealed ASPP2 altered the response patterns of hepatocellular carcinoma HepG2 cells to usnic acid - Yang Wang; Yadong Yan; Yunfei Huo; Yuheng Pang; Liujia Chan; Shanshan Wang; Dexi Chen; Dongdong Lin; Wenjing Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Phosphorus amendment alters soil arbuscular mycorrhizal fungal functional guild compositions in a subtropical forest - Quan-Cheng Wang; Sheng-Sheng Jin; Shanshan Liu; Ge Song; Chunjian Duan; Peng-Peng Lü; Pulak Maitra; Lin Xie; Yongxin Lin; Hang-Wei Hu; Ji-Zheng He; Yong Zheng (Journal of Soils and Sediments, 2023)

Evaluating the aqueous phase obtained from hydrothermal carbonization of municipal sludge as possible liquid fertilizer for plant growth: An analysis of heavy metals and their molecular composition - Guangchun Shan; Weiguang Li; Shanshan Bao; Jie Liu; Lin Zhu; Wenbing Tan (Journal of Cleaner Production, 2023)

Magnetic Z-scheme CuFe2O4/MIL-101(Fe) toward chlorpyrifos degradation: Photocatalytic mechanism, degradation pathways, and intermediates toxicity evaluation - Yu Tian; Qian Liu; Shanshan Lin; Xiaoxia Liang; Sara Khan; Xia Yang; Xianze Wang (Journal of Environmental Chemical Engineering, 2023)

From black water to flushing water: potential applications of chlorine-mediated indirect electrooxidation for ammonia removal - Shanshan Liu; Longqian Xu; Xiaoqing Lin; Jiaming Zhang; Deli Wu (Environmental Science and Pollution Research, 2023)

Response mechanisms of Chlorella sorokiniana to microplastics and PFOA stress: Photosynthesis, oxidative stress, extracellular polymeric substances and antioxidant system - Zhilin Zhao; Xiaoying Zheng; Zongshuo Han; Shanshan Yang; Huijie Zhang; Tao Lin; Chao Zhou (Chemosphere, 2023)

Effects of a calcium/vitamin D/Zinc combination on anti-osteoporosis in ovariectomized rats - Shanshan Wang; Zhen Luo; Hujie Luo; Zhiwei Li; Zhengqiang Yuan; Jian Tang; Li Lin; Zhiyun Du; Jin-Rong Zhou (Journal of Trace Elements in Medicine and Biology, 2023)

In-situ gastritis diagnosis by an oral-administration NIR fluorescent probe with a large Stokes shift and high signal-to-noise ratio - Yanyan Ma; Jie Niu; Xing Liang; Lin Wang; Yimeng Zhang; Hongmin Lv; Tao Wang; Jing Wang; Xiaonan Zhang; Shanshan Xu; Qing Zhu; Zike Jiang; et al. (Chemical Engineering Journal, 2023)

Variable p53/Nrf2 crosstalk contributes to triptolide-induced hepatotoxic process - Zhenyan Hou; Miao Yan; Huixiang Li; Weida Wang; Shen You; Mingjin Wang; Tingting Du; Hui Gong; Wenqun Li; Lin Guo; Shanshan Wei; Bikui Zhang; et al. (Toxicology Letters, 2023)

Effects of persulfate-assisted hydrothermal treatment of municipal sludge on aqueous phase characteristics and phytotoxicity - Guangchun Shan; Weiguang Li; Yujie Zhou; Shanshan Bao; Lin Zhu; Wenbing Tan (Journal of Environmental Sciences, 2023)

Enhanced adsorption of bio-oil on activated biochar in slurry fuels and the adsorption selectivity - Shanshan Yan; Haoran Chen; Haonan Zhu; Zixiang Lin; Gang Wu; Wenran Gao; Hong Zhang; Xun Hu; Junjie Zhang; Shu Zhang; Shoujun Zhang; Yinlong Wu (Fuel, 2023)

Secondary metabolites from marine derived fungus Penicillium chrysogenum Y19-1 with proangiogenic and antithrombotic activities - Peihai Li; Dongxiao Xie; Hao Chen; Yuezi Qiu; Xuanming Zhang; Shanshan Zhang; Lizhen Wang; Houwen Lin; Xiaobin Li; Kechun Liu (Biochemical Systematics and Ecology, 2023)

Investigating the evolution of landscape patterns in historical subdeltas and coastal wetlands in the Yellow River Delta over the last 30 years: A geo-informatics approach - Chao Zhan; Qing Wang; Shanshan Cheng; Lin Zeng; Jiankui Yu; Cheng Dong; Xiang Yu (Frontiers in Marine Science, 2023)
Historically, the river course and coastline of the Yellow River Delta changed frequently, and many studies focused on these change trends and their driving forces. Few studies have explored the influence of historical river channels and historical coastlines on the response of modern landscape patterns. This study examines the impact of channel migration and coastline evolution on the modern landscape pattern of historical subdeltas and coastal wetlands, utilizing a combination of Geo-informatics and Remote Sensing images in 1989, 1998, 2009, and 2016. The results showed that: (1) Subdeltaic landscapes changed from 1998 to 2016, with slight changes in most landscape types in the Ancient Qing Shui Course Subdelta (AQSD), an increase in building sites by 17% in the Zhimai Course Subdelta (ZMSD), a decrease in the proportion of Phragmites/cogongrass communities by 15.8% in the Diao Kou Course Subdelta (DKSD), and domination by natural landscapes in the Modern Qing Shui Course Subdelta (MQSD). (2) Coastal wetlands also experienced changes, with an increase in cultivated land to 60% in the coastal wetlands of CWI, a decline in natural landscapes, and an increase in artificial landscapes in the coastal wetlands of CWII and CWIII, and domination by natural landscapes but an increase in salt fields and culture ponds by 3.45% in the coastal wetlands of CWIV. (3) Channel migration and coastline evolution influenced the direction of landscape succession, causing the landscape-type centroids in the entire delta to move eastward or northward. (4) Throughout the delta, the human tendency to live by rivers was observed. This was due to the availability of freshwater from these rivers, which led to the expansion of inhabited areas and man-made water bodies along the river banks. Channel migration and coastline evolution aggravated the salinization of coastal wetlands and promoted the salt industry and aquaculture in some estuaries of the Yellow River. In general, human activities play a dominant role in shaping the landscape pattern in the Yellow River Delta, but they were largely restricted to historical channel migration and historical coastline evolution.

Kainic acid induced hyperexcitability in thalamic reticular nucleus that initiates an inflammatory response through the HMGB1/TLR4 pathway - Dongbin Li; Xiaosi Zhang; Ruoshi Liu; Meixin Long; Shanshan Zhou; Jinghan Lin; Liming Zhang (NeuroToxicology, 2023)

Wastewater treatment: A universal, scalable and recyclable catalyst with adjustable activity for diverse dyes degradation - Huiqin Zhou; Shanshan Ji; Qinqin Zhang; Weihong Jin; Anlin Feng; Chaoyu Lin; Qingyang Li (Journal of Environmental Management, 2023)

Egg-yolk-derived carbon dots@albumin bio-nanocomposite as multifunctional coating and its application in quality maintenance of fresh litchi fruit during storage - Xianjie Su; Hetong Lin; Bofei Fu; Shanshan Mei; Mengshi Lin; Hongbin Chen; Zongping Zheng; Hangyu Bo; Da-Peng Yang; Yifen Lin (Food Chemistry, 2023)

Structure and hepatoprotective activity of Usp10/NF-κB/Nrf2 pathway-related Morchella esculenta polysaccharide - Shanshan Teng; Yongfeng Zhang; Xinghui Jin; Yanfeng Zhu; Lanzhou Li; Xiaowei Huang; Di Wang; Zhe Lin (Carbohydrate Polymers, 2023)

Deep Sc-RNA sequencing decoding the molecular dynamic architecture of the human retina - Lulin Huang; Runze Li; Lin Ye; Shanshan Zhang; Huaping Tian; Mingyan Du; Chao Qu; Shujin Li; Jie Li; Mu Yang; Biao Wu; Ran Chen; et al. (Science China Life Sciences, 2023)

Tolerance and recovery of aerobic granular sludge: Impact of perfluorooctanoic acid - Xiaoying Zheng; Huijie Zhang; Zhi Xu; Tao Lin; Shanshan Yang; Zhilin Zhao; Zongshuo Han; Chao Zhou (Chemosphere, 2023)

Pu-erh tea alleviated colitis-mediated brain dysfunction by promoting butyric acid production - Shanshan Hu; Zhiyuan Lin; Sibo Zhao; Bowen Zhang; Liyong Luo; Liang Zeng (Food and Chemical Toxicology, 2023)

Highly efficient removal of hexavalent chromium from electroplating wastewater by ferrous/ferric hydroxide complex: From lab-scale to pilot-scale study - Xiaoqing Lin; Longqian Xu; Zhenyu Zhao; Shanshan Liu; Jiaming Zhang; Deli Wu (Chemical Engineering Journal, 2023)

Energy and nutrient recovery by spent mushroom substrate-assisted hydrothermal carbonization of sewage sludge - Guangchun Shan; Weiguang Li; Shanshan Bao; Xinhao Hu; Jie Liu; Lin Zhu; Wenbing Tan (Waste Management, 2023)

Novel multifunctional natural selenium supplement development, in vitro and in vivo analysis, and risk-benefit assessment: Selenium-enriched chicory as a case study - Yaolei Li; Shanshan Ju; Jinjian Huang; Hao Wu; Zhijian Lin; Yu Wang; Hongyu Jin; Shuangcheng Ma; Bing Zhang (Journal of Cleaner Production, 2023)

Geomorphologic evolution of the shallow-buried abandoned Yellow River delta during the last 2000 years - Qing Wang; Lin Zeng; Chao Zhan; Xianbin Liu; Longsheng Wang; Shanshan Cheng; Buli Cui (Frontiers in Marine Science, 2022)
Different from the continuous development of many river deltas since the major Holocene transgression, the modern Yellow River delta (YRD) remained for nearly 1000 years (from 893 AD to 1855 AD) in an abandonment state, until after 1855 AD when it was buried after the Yellow River entered the sea via Lijin. In this study we used optically stimulated luminescence (OSL) dating and grain size and sedimentary facies analysis of four borehole cores, combined with an analysis of landform morphology, to reconstruct the history of the ancient abandoned YRD. The results indicate that after the delta was abandoned due to the reduced sediment supply by the Yellow River in 893 AD, a sandy coast developed under the influence of wave erosion, and offshore shell ridges were formed beyond the coastline. During the interval from the Medieval Warm Period (MWP) to the Little Ice Age (LIA), driven by climate change and storm surges, the shell ridges migrated laterally, widened and rose, while sediment accumulation in the landward-side interfluvial floodplains was relatively weak. This configuration subsequently constituted a coastal highland – plain depression system. After 1077 AD, this system, together with the abandoned delta, was eroded by the Daqing River estuary. After 1855 AD, the abandoned delta landform system was completely buried by Yellow River sediments, and the wave-controlled sandy coast was transformed to a tide-controlled silt-mud coast. We summarize these findings in the form of a geomorphic model of the evolution of the abandoned delta from the MWP to the LIA. Overall, our results highlight the geomorphic effects of the sediment-laden river delta and the response of the abandoned delta geomorphic system on the millennial timescale, and they provide a theoretical foundation for predicting the geomorphic evolution of a major river delta on different timescales, against the background of global change.

Hippocampal Iron Accumulation Impairs Synapses and Memory via Suppressing Furin Expression and Downregulating BDNF Maturation - Yating Zhang; Xue Bai; Yi Zhang; Shanshan Yao; Yiduo Cui; Lin-Hao You; Peng Yu; Yan-Zhong Chang; Guofen Gao (Molecular Neurobiology, 2022)

Spatial patterns and driving factors of carbon stocks in mangrove forests on Hainan Island, China - Yuchen Meng; Ruikun Gou; Jiankun Bai; David Moreno‐Mateos; Charles C. Davis; Luoma Wan; Shanshan Song; Hongsheng Zhang; Xiaoshan Zhu; Guanghui Lin (Global Ecology and Biogeography, 2022)
Aim Mangrove forests are important coastal wetlands for the blue carbon budget and play a significant role in mitigating global climate change. However, spatial patterns of carbon stocks in mangrove forests on an island scale have not been quantified owing to methodological limitations and lack of understanding of controlling factors. We took the entire Hainan Island as a case study and aimed to carry out a comprehensive investigation of the spatial patterns and driving factors of carbon stocks in mangrove forests. Location Southern China. Time period 2017–2020. Major taxa studied Mangrove forest. Methods The upscaling method combined with field surveys and Sentinel‐2 imagery analysis were used to compare different models for optimization of mangrove ecosystem carbon stock estimations. We also used structural equation modelling (SEM) to evaluate the factors driving the distributional patterns of mangrove carbon stocks on an island scale. Results The current total mangrove carbon stock of the entire Hainan Island was estimated to be 703,181 Mg C (with a mean density of 192 Mg C/ha), with the above‐ and below‐ground carbon stocks averaging at 44.7 and 147.3 Mg C/ha, respectively. The mangrove carbon storage in the north‐eastern region of the island was the highest and in the west region the lowest. Sediment nitrogen content and plant species diversity had the most positive driving effects on the distribution of total carbon stock for Hainan Island mangroves. Main conclusions The combination of field surveys and Sentinel‐2 imagery analysis can be applied to regional‐scale estimations of carbon stocks for mangrove forests. Spatial pattens of mangrove carbon stocks vary among locations on Hainan Island, and soil nutrient (especially nitrogen) availability is the dominant factor regulating carbon stock variations along the land‐to‐sea gradient. Our findings have significant implications for better understanding the distribution of mangrove carbon stocks and quantification of the global blue carbon budget.

The efficacy and safety of TNF inhibitor (golimumab) as salvage treatment in patients with refractory noninfectious uveitis - Yi Jin; Shanshan Lu; You Lin; Xiaoyue Mou (Inflammopharmacology, 2022)

Preliminary study of genome-wide association identified novel susceptibility genes for thyroid-related hormones in Chinese population - Liang Huang; Fenghua Bai; Yutian Zhang; Shanshan Zhang; Tianbo Jin; Xingwei Wei; Xiaoli Zhou; Mei Lin; Yufei Xie; Chanyi He; Qi Lin; Tian Xie; et al. (Genes & Genomics, 2022)

Transformation of HBCDs by Rhodococcus sp. stu-38 - Fei Yu; Wenqi Luo; Yuyang Li; Shanshan Meng; Xianbin Lin; Lele Li; Xueying Ye; Hui Wang; Tao Peng; Tongwang Huang; Zhong Hu (Current Microbiology, 2022)

Preliminary study of genome-wide association identifies novel susceptibility genes for serum mineral elements in the Chinese Han population - Duojian Guo; Yu Zhou; Xingwei Wei; Shanshan Zhang; Tianbo Jin; Yutian Zhang; Mei Lin; Xiaoli Zhou; Yufei Xie; Chanyi He; Qi Lin; Ping He; et al. (Biological Trace Element Research, 2022)

Proteomic characterization of four subtypes of M2 macrophages derived from human THP-1 cells - Pengfei Li; Chen Ma; Jing Li; Shanshan You; Liuyi Dang; Jingyu Wu; Zhifang Hao; Jun Li; Yuan Zhi; Lin Chen; Shisheng Sun (Journal of Zhejiang University-SCIENCE B, 2022)

Trimetazidine affects pyroptosis by targeting GSDMD in myocardial ischemia/reperfusion injury - Xudong Chen; Shuang Lin; Shanshan Dai; Jibo Han; Peiren Shan; Weiqi Wang; Zhouqing Huang; Bozhi Ye; Weijian Huang (Inflammation Research, 2022)

PHD2 attenuates high-glucose-induced blood retinal barrier breakdown in human retinal microvascular endothelial cells by regulating the Hif-1α/VEGF pathway - Jia Li; Xi Lu; Liqing Wei; Dan Ye; Jianqiang Lin; Xiaoyu Tang; Kaixuan Cui; Shanshan Yu; Yue Xu; Xiaoling Liang (Inflammation Research, 2022)

Air pollution increased risk of reproductive system diseases: a 5-year outcome analysis of different pollutants in different seasons, ages, and genders - Ya Li; Juan Du; Shanshan Lin; Huihui He; Rui Jia; Weihong Liu (Environmental Science and Pollution Research, 2022)

Streptomyces luteolifulvus sp. nov., a novel actinomycete isolated from soil in Nanjing, China - Shanshan Zhao; Ming Cheng; Congyu Lin; He Liu; Zhengran Wang; Kai Zhang; Simin Song; Qian Yang (Antonie van Leeuwenhoek, 2021)

Master regulator NtrC controls the utilization of alternative nitrogen sources in Pseudomonas stutzeri A1501 - Zhimin Yang; Qin Li; Yongliang Yan; Xiubin Ke; Yueyue Han; Shaoyu Wu; Fanyang Lv; Yahui Shao; Shanshan Jiang; Min Lin; Yunhua Zhang; Yuhua Zhan (World Journal of Microbiology and Biotechnology, 2021)
Pseudomonas stutzeri A1501 is a model strain used to study associative nitrogen fixation, and it possesses the nitrogen regulatory NtrC protein in the core genome. Nitrogen sources represent one of the important factors affecting the efficiency of biological nitrogen fixation in the natural environment. However, the regulation of NtrC during nitrogen metabolism in P. stutzeri A1501 has not been clarified. In this work, a phenotypic analysis of the ntrC mutant characterized the roles of NtrC in nitrogen metabolism and the oxidative stress response of P. stutzeri A1501. To systematically identify NtrC-controlled gene expression, RNA-seq was performed to further analyse the gene expression differences between the wild-type strain and the ∆ ntrC mutant under nitrogen fixation conditions. A total of 1431 genes were found to be significantly altered by ntrC deletion, among which 147 associative genes had NtrC-binding sites, and the pathways for nitrogen fixation regulation, nitrogenous compound acquisition and catabolism and nitrate assimilation were discussed. Furthermore, the oxidative stress-related gene ( katB ), which was upregulated by ntrC deletion, was suggested to be a potential target gene of NtrC, thus highlighting the importance of NtrC in nitrogenase protection against oxygen damage. Based on these findings, we propose that NtrC is a high-ranking element in the regulatory network of P. stutzeri A1501 that controls a variety of nitrogen metabolic and oxidative stress responsive traits required for adaptation to complex rhizosphere environments.

Astragaloside IV alleviates atherosclerosis through targeting circ_0000231/miR-135a-5p/CLIC4 axis in AS cell model in vitro - Xiao Shao; Zhaozheng Liu; Shanshan Liu; Na Lin; Yue Deng (Molecular and Cellular Biochemistry, 2021)

High expression of NEK2 promotes lung cancer progression and drug resistance and is regulated by mutant EGFR - Chuanhui Chen; Shanshan Peng; Penghui Li; Lin Ma; Xin Gan (Molecular and Cellular Biochemistry, 2020)

Applying Iterative Method to Solving High-Order Terms of Seafloor Topography - Diao Fan; Shanshan Li; Shuyu Meng; Yi Lin; Zhibin Xing; Chi Zhang; Junjun Yang; Xiaoyun Wan; Zhenhao Qu (Marine Geodesy, 2020)

Transport and numerical simulation of Cu2+ in saturated porous medium in the presence of magnetic nanoparticles - Shihui Song; Yinghao Song; Mengdi Shi; Zheng Hu; Tianyu Li; Shanshan Lin (Environmental Science and Pollution Research, 2019)

Effect of Different Glucose Concentrations on Small RNA Levels and Adherence of Streptococcus mutans - Shanshan Liu; Yan Zhou; Ye Tao; Peilin Zhuang; Liangyue Pang; Qinghui Zhi; Huancai Lin (Current Microbiology, 2019)

Isolation and identification of the Raoultella ornithinolytica-ZK4 degrading pyrethroid pesticides within soil sediment from an abandoned pesticide plant - Xiaoqing Zhang; Xiangxiang Hao; Shanshan Huo; Wanzhong Lin; Xinxin Xia; Kuai Liu; Bihua Duan (Archives of Microbiology, 2019)

Plants alter their vertical root distribution rather than biomass allocation in response to changing precipitation - Bingwei Zhang; Marc W. Cadotte; Shiping Chen; Xingru Tan; Cuihai You; Tingting Ren; Minling Chen; Shanshan Wang; Weijing Li; Chengjin Chu; Lin Jiang; Yongfei Bai; et al. (Ecology, 2019)
Elucidating the variation of allocation pattern of ecosystem net primary productivity ( NPP ) and its underlying mechanisms is critically important for understanding the changes of aboveground and belowground ecosystem functions. Under optimal partitioning theory, plants should allocate more NPP to the organ that acquires the most limiting resource, and this expectation has been widely used to explain and predict NPP allocation under changing precipitation. However, confirmatory evidence for this theory has mostly come from observed spatial variation in the relationship between precipitation and NPP allocation across ecosystems, rather than directly from the influences of changing precipitation on NPP allocation within systems. We performed a 6‐yr five‐level precipitation manipulation experiment in a semiarid steppe to test whether changes in NPP allocation can be explained by the optimal partitioning theory, and how water requirement of plant community is maintained if NPP allocation is unaltered. The 30 precipitation levels (5 levels × 6 yr) were divided into dry, nominal, and wet precipitation ranges, relative to historical precipitation variation over the past six decades. We found that NPP in both aboveground ( ANPP ) and belowground ( BNPP ) increased nonlinearly as precipitation increased, while the allocation of NPP to BNPP ( f BNPP ) showed a concave quadratic relationship with precipitation. The declined f BNPP as precipitation increased in the dry range supported the optimal partitioning theory. However, in the nominal range, NPP allocation was not influenced by the changed precipitation; instead, BNPP was distributed more in the surface soil horizon (0–10 cm) as precipitation increased, and conversely more in the deeper soil layers (10–30 cm) as precipitation decreased. This response in root foraging appears to be a strategy to satisfy plant water requirements and partially explains the stable NPP allocation patterns. Overall, our results suggest that plants can adjust their vertical BNPP distribution in response to drought stress, and that only under extreme drought does the optimal partitioning theory strictly apply, highlighting the context dependency of the adaption and growth of plants under changing precipitation.

Spatial Distribution and Congener Profiles of Polybrominated Diphenyl Ethers in Surface Sediment from Sanmen Bay and Xiamen Bay, Southeast China - Kunyan Liu; Yong Qiu; Shanshan Zhou; Kunde Lin; Da Chen; Han Qu; Xiaodong Wang; Yongxia Hu; Yan Wang (Bulletin of Environmental Contamination and Toxicology, 2019)

Protective Effects of Salidroside on Lead Acetate-induced Oxidative Stress and Hepatotoxicity in Sprague-Dawley Rats - Chen Chen; Beibei Lin; Shanshan Qi; Jia He; Hongxing Zheng (Biological Trace Element Research, 2019)

A single water molecule accelerating the atmospheric reaction of HONO with ClO - Shanshan Tang; Lin Du (Environmental Science and Pollution Research, 2019)

Microvesicles derived from human bone marrow mesenchymal stem cells promote U2OS cell growth under hypoxia: the role of PI3K/AKT and HIF-1α - Shanshan Lin; Bo Zhu; Guozhi Huang; Qing Zeng; Chuhuai Wang (Human Cell, 2019)

Effects of IPT or NDGA Application on ABA Metabolism and Maturation in Grape Berries - Hong Lin; Shanshan Wang; Takanori Saito; Katsuya Ohkawa; Hitoshi Ohara; Ampa Kongsuwan; Haifeng Jia; Yinshan Guo; Hiroyuki Tomiyama; Satoru Kondo (Journal of Plant Growth Regulation, 2018)

White matter integrity correlates with residual consciousness in patients with severe brain injury - Lubin Wang; Yi Yang; Shanshan Chen; Mingmei Ge; Jianghong He; Zheng Yang; Pan Lin; Xinhuai Wu (Brain Imaging and Behavior, 2018)

Screening and Genome Sequencing of Deltamethrin-Degrading Bacterium ZJ6 - Xiangxiang Hao; Xiaoqing Zhang; Bihua Duan; Shanshan Huo; Wanzhong Lin; Xinxin Xia; Kuai Liu (Current Microbiology, 2018)

Survival rate and population size of Indo‐Pacific humpback dolphins ( Sousa chinensis ) in Xiamen Bay, China - Bingyao Chen; Huili Gao; Thomas A. Jefferson; Yi Lu; Lin Wang; Shanshan Li; Hui Wang; Xinrong Xu; Guang Yang (Marine Mammal Science, 2018)
The survival rate and population size of Indo‐Pacific humpback dolphins ( Sousa chinensis ) in Xiamen, China, were estimated from vessel‐based surveys during 2007–2010. Over the course of 202 d (881.1 observation hours), 76 groups were observed, and 52 dolphins were successfully identified. The Cormack‐Jolly‐Seber model estimated a constant apparent survival of 0.948 (95% CI: 0.922–0.966). Based on the open/POPAN model, the population size was estimated at 70 individuals (95% CI: 63–88). To explore the effect of uneven yearly survey effort, we pooled the data with seven sampling occasions with similar effort. This data set generated similar results of a constant survival of 0.957 (95% CI: 0.918–0.978) and population size of 72 (95% CI: 65–88). The small population size of the Xiamen humpback dolphins satisfies the Critically Endangered criterion of IUCN (D), and emphasizes urgency of the need for protection of the population. Improved monitoring efforts should be focused on enhancing our understanding of current status and evaluating impacts of all anthropogenic activities. A conservation plan for the population should also be drawn up.

Study on hydrothermal deactivation of Pt/MnO x -CeO2 for NO x -assisted soot oxidation: redox property, surface nitrates, and oxygen vacancies - Hailong Zhang; Shanshan Li; Qingjin Lin; Xi Feng; Yaoqiang Chen; Jianli Wang (Environmental Science and Pollution Research, 2018)

Enhanced Tumor Diagnostic and Therapeutic Effect of Mesoporous Silica Nanoparticle-Mediated Pre-targeted Strategy - Gaochao Lv; Ke Li; Ling Qiu; Ying Peng; Xueyu Zhao; Xi Li; Qingzhu Liu; Shanshan Wang; Jianguo Lin (Pharmaceutical Research, 2018)

Secretion of Down Syndrome Critical Region 1 Isoform 4 in Ischemic Retinal Ganglion Cells Displays Anti-Angiogenic Properties Via NFATc1-Dependent Pathway - Yue Xu; Boyu Yang; Yaguang Hu; Lin Lu; Xi Lu; Jiawei Wang; Qinmeng Shu; Qiaochu Cheng; Shanshan Yu; Fan Xu; Jingjing Huang; Xiaoling Liang (Molecular Neurobiology, 2017)

Population transcriptomes reveal synergistic responses of DNA polymorphism and RNA expression to extreme environments on the Qinghai–Tibetan Plateau in a predatory bird - Shengkai Pan; Tongzuo Zhang; Zhengqin Rong; Li Hu; Zhongru Gu; Qi Wu; Shanshan Dong; Qiong Liu; Zhenzhen Lin; Lucia Deutschova; Xinhai Li; Andrew Dixon; et al. (Molecular Ecology, 2017)
Low oxygen and temperature pose key physiological challenges for endotherms living on the Qinghai–Tibetan Plateau ( QTP ). Molecular adaptations to high‐altitude living have been detected in the genomes of Tibetans, their domesticated animals and a few wild species, but the contribution of transcriptional variation to altitudinal adaptation remains to be determined. Here we studied a top QTP predator, the saker falcon, and analysed how the transcriptome has become modified to cope with the stresses of hypoxia and hypothermia. Using a hierarchical design to study saker populations inhabiting grassland, steppe/desert and highland across Eurasia, we found that the QTP population is already distinct despite having colonized the Plateau cDNA level, but of only seventeen genes identified, three function in hypoxia and four in immune response. Our results show a significant role for RNA transcription: 50% of upregulated transcription factors were related to hypoxia responses, differentiated modules were significantly enriched for oxygen transport, and importantly, divergent EPAS 1 functional variants with a refined co‐expression network were identified. Conservative gene expression and relaxed immune gene variation may further reflect adaptation to hypothermia. Our results exemplify synergistic responses between DNA polymorphism and RNA expression diversity in coping with common stresses, underpinning the successful rapid colonization of a top predator onto the QTP . Importantly, molecular mechanisms underpinning highland adaptation involve relatively few genes, but are nonetheless more complex than previously thought and involve fine‐tuned transcriptional responses and genomic adaptation.

Disruption of non-anchored cell wall protein NCW-1 promotes cellulase production by increasing cellobiose uptake in Neurospora crassa - Liangcai Lin; Yong Chen; Jingen Li; Shanshan Wang; Wenliang Sun; Chaoguang Tian (Biotechnology Letters, 2017)

Measurement and calculation of crown projection area and crown volume of individual trees based on 3D laser-scanned point-cloud data - Wenshu Lin; Yuan Meng; Zhaowen Qiu; Shanshan Zhang; Jinzhuo Wu (International Journal of Remote Sensing, 2017)

Properties of root exudates and rhizosphere sediment of Bruguiera gymnorrhiza (L.) - Beibei Liu; Xinyu Liu; Shanshan Huo; Xin Chen; Lin Wu; Miao Chen; Kaibo Zhou; Qinfen Li; Lixu Peng (Journal of Soils and Sediments, 2017)

WSL3, a component of the plastid-encoded plastid RNA polymerase, is essential for early chloroplast development in rice - Liwei Wang; Chunming Wang; Yihua Wang; Mei Niu; Yulong Ren; Kunneng Zhou; Huan Zhang; Qibing Lin; Fuqing Wu; Zhijun Cheng; Jiulin Wang; Xin Zhang; et al. (Plant Molecular Biology, 2016)

Wax crystal-sparse leaf 3 encoding a β-ketoacyl-CoA reductase is involved in cuticular wax biosynthesis in rice - Lu Gan; Xiaole Wang; Zhijun Cheng; Linglong Liu; Jiulin Wang; Zhe Zhang; Yulong Ren; Cailin Lei; Zhichao Zhao; Shanshan Zhu; Qibing Lin; Fuqing Wu; et al. (Plant Cell Reports, 2016)

Anti-angiogenic and anti-inflammatory effect of Magnolol in the oxygen-induced retinopathy model - Boyu Yang; Yue Xu; Shanshan Yu; Yongsheng Huang; Lin Lu; Xiaoling Liang (Inflammation Research, 2016)

Predicting biofilm thickness and biofilm viability based on the concentration of carbon-nitrogen-phosphorus by support vector regression - Shanshan Lin; Xinmin Wang; Yunlong Chao; Yude He; Ming Liu (Environmental Science and Pollution Research, 2016)

Immunological markers predict the prognosis of patients with squamous non-small cell lung cancer - Long Jiang; Zerui Zhao; Shanshan Jiang; Yongbin Lin; Han Yang; Zehua Xie; Yaobin Lin; Hao Long (Immunologic Research, 2015)

The NPR1 homolog GhNPR1 plays an important role in the defense response of Gladiolus hybridus - Xionghui Zhong; Lin Xi; Qinglong Lian; Xian Luo; Ze Wu; Shanshan Seng; Xue Yuan; Mingfang Yi (Plant Cell Reports, 2015)

Gender differences in affective sharing and self–other distinction during empathic neural responses to others’ sadness - Pinchao Luo; Junfang Wang; Yan Jin; Shanshan Huang; Mengshu Xie; Lin Deng; Juncong Fang; Xiaochun Zheng; Xiaoying Chen; Yue Li; Yijie Jiang; Xifu Zheng (Brain Imaging and Behavior, 2015)

Diacylglycerol Kinase (DGK) Inhibitor II (R59949) Could Suppress Retinal Neovascularization and Protect Retinal Astrocytes in an Oxygen-Induced Retinopathy Model - Lu Yang; Yue Xu; Weihua Li; Boyu Yang; Shanshan Yu; Huanjiao Zhou; Cheng Yang; Fan Xu; Jun Wang; Yi Gao; Yongsheng Huang; Lin Lu; et al. (Journal of Molecular Neuroscience, 2015)

Improved activity of the Cel5A endoglucanase in Saccharomyces cerevisiae deletion mutants defective in oxidative stress defense mechanisms - Guochao Wu; Jintang Sun; Shanshan Yu; Quanchao Dong; Guoqiang Zhuang; Weifeng Liu; Jianqiang Lin; Yinbo Qu (Biotechnology Letters, 2015)

Differences in sex reversion and growth between normal and neomale stock in half-smooth tongue sole, Cynoglossus semilaevis - Qiaomu Hu; Song-Lin Chen; Fengtao Gao; Yangzhen Li; Shanshan Liu; Feng Liu; Jingfeng Yang; Min Du (Aquaculture International, 2014)

Genetic diversity and structure of the Fusarium oxysporum f.sp. lini populations on linseed (Linum usitatissimum) in China - Lin Yuan; Na Mi; Shanshan Liu; Hui Zhang; Ziqin Li (Phytoparasitica, 2013)

The distribution and sea–air transfer of volatile mercury in waste post-desulfurization seawater discharged from a coal-fired power plant - Lumin Sun; Shanshan Lin; Lifeng Feng; Shuyuan Huang; Dongxing Yuan (Environmental Science and Pollution Research, 2013)

Macrobenthic community in the Xiaoqing River Estuary in Laizhou Bay, China - Xianxiang Luo; Shanshan Zhang; Jianqiang Yang; Jinfen Pan; Lin Tian; Longjun Zhang (Journal of Ocean University of China, 2013)

A potentially novel reovirus isolated from swine in northeastern China in 2007 - Chaofan Zhang; Licheng Liu; Pengzhi Wang; Shanshan Liu; Wencheng Lin; Feng Hu; Weili Wu; Weijun Chen; Shangjin Cui (Virus Genes, 2011)

Molecular cloning and expression analysis of a new putative gene encoding 3-hydroxy-3-methylglutaryl-CoA synthase from Salvia miltiorrhiza - Lin Zhang; Xiangming Yan; Jing Wang; Shanshan Li; Pan Liao; Guoyin Kai (Acta Physiologiae Plantarum, 2011)

Recent progress in studies on land cover change and its regional climatic effects over China during historical times - Jingyun Zheng; Shanshan Lin; Fanneng He (Advances in Atmospheric Sciences, 2009)

Gridding cropland data reconstruction over the agricultural region of China in 1820 - Shanshan Lin; Jingyun Zheng; Fanneng He (Journal of Geographical Sciences, 2009)

Specific Phage-Displayed Peptides Binding to Tumor Vasculature - Yu Han; Liu Hong; Kaichun Wu; Shuhui Liang; Lin Xia; Shanshan Cao; Huihong Zhai; Jun Wang; Lijie He; Feihu Bai; Zhen Chen; Taidong Qiao; et al. (International Journal of Peptide Research and Therapeutics, 2006)

Pollution characteristics of the rivers in suburban Shanghai - Chunxia Yao; Zhenlou Chen; Shiyuan Xu; Ling Li; Li Wang; Shanshan Lin (Journal of Geographical Sciences, 2005)